Towards Simon O’Sullivan, On the Production of Subjectivity: Five Diagrams of the Finite-Infinite Relation - Sadiku, Artan (Identities: Journal for Politics, Gender and Culture, 2013)
Author(s): Artan Sadiku Title (English): Towards Simon O’Sullivan, On the Production of Subjectivity: Five Diagrams of the Finite-Infinite Relation Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 139-140 Page Count: 2 Citation (English): Artan Sadiku, “Towards Simon O’Sullivan, On the Production of Subjectivity: Five Diagrams of the Finite-Infinite Relation,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 139-140.